Political Aspects of Public Administration in the Public Sector of Ukraine - Bolotina, Ye.; Shubna, O.; Кvasha, A.; Melchenko, V. (Економічний вісник Донбасу, 2021)
The article reveals the basic theoretical principles of public administration. The stages of formation and development of public administration are studied. It was found that public administration, as a system of public administration in Ukraine, needs to be reformed in a market economy and democratization of society. The main problems of formation and development of the system of public administration in terms of compliance with the European political trend of integration of public and personal factors, expanding the sphere of state influence while maximizing rights and freedoms, absolutization of the administrative factor of social transformations are considered. It is established that public administration: provides implements the decisions of the authorities; applies democratic, public, liberal forms and methods of managing the social, social and economic development of the country. The main factors that influenced the emergence in many countries of the world of such a new form of government in the public sector as public administration. Based on the understanding of the peculiarities of the evolution of the management model in the public sector, the need to introduce the concept of "public administration" into scientific circulation is substantiated. Recommendations for decentralization of management in the context of domestic reforms to increase the efficiency of the system of public authorities on an innovative basis are offered. In this context, it is extremely important to implement initiatives on constitutional changes in the decentralization of power, the priorities of the Public Administration Reform Strategy of Ukraine for 2016-2020; development of a new version of the Law of Ukraine "On Civil Service", which regulates the basic principles, legal and organizational principles of public service.